2019
DOI: 10.24912/jm.v23i3.570
|View full text |Cite
|
Sign up to set email alerts
|

The Differences in Risk Perception between Millennials and Baby Boomers in Online Transactions

Abstract: This study aims to distinguish the risks perceived by the millennial generation and the risks perceived by baby boomer generations when transacting online. The number of samples used in this study was one hundred thirty-five respondents. Criteria for respondents are people who have done online transactions in the generation being studied. This study uses a discriminant analysis conducted by a study of three types of risk perceived by respondents, product risk, financial risk, and shipping risk. The result show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…The most important variable which made a statistically unique contribution, as a predictor of total prevention behavior in this case, was the perceived risk across generations. This finding is consistent with the literature ( Krewski et al, 2006 ; Tandi et al, 2018 ; Morgan et al, 2019 ; Mulia, 2019 ). Furthermore, in regards to preventive behavior, COVID-19 health anxiety was positively associated and automatic negative thoughts were negatively associated predictors.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The most important variable which made a statistically unique contribution, as a predictor of total prevention behavior in this case, was the perceived risk across generations. This finding is consistent with the literature ( Krewski et al, 2006 ; Tandi et al, 2018 ; Morgan et al, 2019 ; Mulia, 2019 ). Furthermore, in regards to preventive behavior, COVID-19 health anxiety was positively associated and automatic negative thoughts were negatively associated predictors.…”
Section: Discussionsupporting
confidence: 94%
“…Demographic variables and disease knowledge were previously investigated in the literature, but less was comprehensively written on the specific psychological variables chosen in this study (perceived risk, COVID-19 health anxiety, negative automatic thoughts, and psychological flexibility). One of the most researched psychological factor from the targeted variables was the perceived risk, which has a statistically significant association with prevention behavior ( Mulia, 2019 ; Asmundson and Taylor, 2020 ; Dryhurst et al, 2020 ). Health anxiety, automatic negative thoughts and psychological flexibility were analyzed in the context of mental health issues and COVID-19, but they were not specifically linked to prevention behavior and this approach that we took, highlighted many new and diverse statistically significant associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual risk perception is tied to the utilization of prevention techniques, which can stop the spread of the virus (Dryhurst et al, 2020). The results of the study led by Mulia (2019) demonstrated a diversity in risk perception of COVID-19 between different generations. According to Morgan et al (2019) higher perceived risk was found in the older participants.…”
Section: Introductionmentioning
confidence: 99%
“…Dimana kualitas pelayanan yang baik akan menumbuhkan kepuasan pelanggan, seperti yang dilakukan blue bird dan grab (Apriyani dan Mahmudi, 2019). Dalam produk jasa, persepsi konsumen terasosiasi langsung dengan perusahaan melalui merek, diasumsikan bahwa persepsi risiko tetap sama tanpa memperhatikan kredibilitas dari masing-masing platform e-commerce (Mulia, 2019). Maka dari itu, merek suatu perusahaan jasa menjadi sangat penting, terutama dalam menghadapi persaingan, mengingat karakter jasa yang intangible, dimana konsumen melihat merek pada perusahaan jasa sebagai harapan atau persepsi dan pembelian jasa yang mereka lakukan sama saja dengan membeli merek dari perusahaan, maka dari itu citra merek dari sebuah perusahaan jasa sangatlah penting.…”
Section: Introductionunclassified